THERMAL CHARACTERIZATION OF PLA, ABS, PETG, AND NYLON FILAMENTS FOR 3D PRINTING APPLICATIONS - de Oliveira, Alexandre Melo; Gonçalves, Lindomar Matias; Gomides, Luciana de Melo; Mesquita, Amir Zacarias; Magosse, Gabriel Boni (Seven Editora, 2025)
This study investigates the thermal characterization of PLA, ABS, PETG, and Nylon filaments, widely used in 3D printing, to understand their behavior during additive manufacturing processes. Thermogravimetry (TGA) and differential scanning calorimetry (DSC) were employed to assess key thermal properties, including thermal stability, glass transition temperatures, and melting points. The research also examined how printing temperature affects the mechanical and dimensional stability of fabricated parts. Experiments involved 23 polymer samples, including virgin and recycled PLA, to evaluate sustainability and material performance. A 3D printer equipped with precise thermal control and calibrated analytical instruments ensured accurate evaluations. Results highlighted correlations between thermal properties and the quality of printed components, providing data to optimize print settings and minimize defects. The findings contribute to advancing sustainable 3D printing practices by identifying efficient material usage and reducing waste. This project addresses industrial needs for high-quality additive manufacturing, emphasizing eco-friendly material development and the importance of standardizing thermophysical data for improved processes and products.DOI: https://doi.org/10.56238/sevened2025.026-025